CERTAINTY ESTABLISHED: MAJORITARIANISM TRUMPS MINORITY, PASSES CONSTITUTIONAL MUSTER, AND ACCORDS WITH INTERNATIONAL STANDARDS Association of Mineworkers and Construction v Royal Bafokeng Platinum Limited [2020] ZAAC 1 - William Manga Mokofe (Obiter, 2023)
South African courts have recognised majoritarianism to mean that the will of the majority is favoured over the will of the minority in serving the legislative goals of advancing labour peace, orderly collective bargaining, and the democratisation of the workplace. Yet a fundamental problem arising from majoritarianism is the possibility that the rights of the minority could be violated. This case involves the retrenchments in South Africa when a firm elects to dismiss part of its labour force for operational reasons. This procedure frequently arises without warning. Generally, it has devastating consequences and leaves certain employees out of work through no fault of their own. That is exactly what happened in Association of Mineworkers and Construction v Royal Bafokeng Platinum Limited [2020] ZACC 1.Against this backdrop, this case note addresses two issues. First, it explores the constitutionality of procedural fairness during retrenchments; second, it assesses the International Labour Organisation’s Committee of the Freedom of Association (ILO-CFA) Report on this matter against the decision of the Committee.